Comparative study of fluoride conversion coatings formed on biodegradable powder metallurgy Mg: The effect of chlorides at physiological level - Pereda, María Dolores (2011)
The development of a biodegradable metallic implant demands a precisely defined degradation profile and adequate mechanical properties. Mg has been proposed for this purpose but it has an excessively high corrosion rate and insufficient yield strength. In the present work pure Mg mechanically reinforced by a powder metallurgy (Mg(PM)) route and treated with KF was used. The effect of chlorides, at the physiological level, on four fluoride conversion coatings (F-CC) formed on Mg(PM) was evaluated comparatively. The behavior of Mg(PM) during fluoride treatments (0.01 M–0.3 M fluoride-containing solutions) before and after the addition of chlorides (8 g L− 1 NaCl) was investigated by conventional corrosion techniques and by scanning electrochemical microscopy (SECM) complemented with SEM observations and EDX analysis. Results showed that the composition and the microstructural characteristics of the F-CCs as well as their corrosion behavior change with KF concentration and immersion time. Treatments in the 0.01 M–0.1 M KF range prove to be effective to protect Mg(PM) against corrosion in the absence of chlorides while higher KF solution concentration (0.3 M) adversely affects the corrosion resistance of this metal. In the presence of chloride ions the F-CCs progressively lose their fluoride content and their corrosion resistance at a rate that depends on the treatment conditions. Such temporary corrosion protection is appropriate for biodegradable implants.